An integrated ISM-PLS model for green human resources management practices. (17th March 2022) - Ardakani, Davod Andalib; Bagheri, Moslem; Kiani, Mehrdad; Soltanmohammadi, Asieh
This study proposed a model for green human resources management (GHRM) practices. In doing so, primarily, the literature was systematically reviewed through the meta-synthesis method, and then GHRM practices and activities were extracted and categorised. Next the practices were divided into level partitions through ISM, and the relationships between them were identified. At the final stage, structural equation modelling was used to assess the quality of the proposed method through the PLS-PM approach in R software. Next the relationships between the model dimensions were examined. The findings revealed 48 indicators falling under eight dimensions. The level partitions of the model, too, revealed that in the lowest level, 'green jobs analysis' left the greatest impact on the other dimensions, whereas 'employee relations and green participation' was placed in the highest level. Finally, the findings of the PLS-PM approach showed the goodness of fit of the measurement and structural model.